2017
DOI: 10.18203/2349-3291.ijcp20172112
|View full text |Cite
|
Sign up to set email alerts
|

Study of risk factors of severe acute malnutrition (SAM) in children 6 months to 5 years of age and evaluation of effect of micronutrient supplementation (WHO protocol) on serum zinc and magnesium levels: a case control study

Abstract: Background: Although risk factors for malnutrition have been identified earlier, individual factors potentially change in specific areas over time and a current characterization of risk factors provide the basis for preventative intervention strategies. No guidelines in relation to duration of micronutrient supplementation for treatment of SAM are available. Thus, the study was done to know the adequacy of dose of micronutrients that are presently being supplemented (WHO Protocols) for treating SAM. Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…With-holding colostrum was a risk factor for underweight at 6 months of age in our study. Infants fed colostrum had better nutritional status than those who did not which is consistent with the previous studies [20]. In this study, irregular antenatal checkups have shown a significant relationship with SAM, as shown in other studies also [21].…”
Section: Discussionsupporting
confidence: 93%
“…With-holding colostrum was a risk factor for underweight at 6 months of age in our study. Infants fed colostrum had better nutritional status than those who did not which is consistent with the previous studies [20]. In this study, irregular antenatal checkups have shown a significant relationship with SAM, as shown in other studies also [21].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, children with small birth weights are often born to households with low socioeconomic status and mothers with poor health conditions [ 36 ]. Due to the irregular distribution of food for children in poverty-stricken households, and the knowledge gap of parents/caregivers for adequate micronutrient supplementation, children can be deprived of nutritious food intake and eventually suffer from acute undernutrition [ 12 , 14 ]. Again, parental illiteracy is frequently connected with low birth weight and other variables, such as inadequate maternal healthcare access and child caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for single malnutrition indicators (i.e. stunting, wasting or underweight) are multifaced ranging from access to nutrients, socio-demographic factors, poverty, access to healthcare and geographical location [3,9,10,11,12]. However, determinants of coexistence of stunting, wasting and underweight is not previously explored particularly in Bangladesh to inform context-speci c evidence-based prevention strategies.…”
Section: Introductionmentioning
confidence: 99%